Natural fiber as a fibrous reinforced in polymer modified mortar : a review / Azamuddin Husin, Mahyuddin Ramli and Cheah Chee Ban - Husin, Azamuddin; Ramli, Mahyuddin; Cheah, Chee Ban (2015)
The disadvantages of cement based material are due to its brittleness, thus perform low tensile strength and poor fracture toughness. This poor performance can be improved by using fiber as reinforcement. Fiber such as carbon fiber, glass fiber is widely used to enhance the properties of the cement-based material, especially in the form of thin sheet/plates. While global scenario has intensively moved towards green buildings, it is possible to use our local resources. It is to innovate local green building materials such as using natural fiber from agricultural waste such as oil palm fiber, coir fiber, kenaf and wood fiber. Therefore, this paper highlights the review of the literature regarding the use of natural fiber in polymer-modified mortar.